PENGARUH RETURN SAHAM, VOLUME PERDAGANGAN DAN VOLATILITAS HARGA SAHAM TERHADAP BID-ASK SPREAD PADA PERUSAHAAN YANG MELAKUKAN STOCK SPLIT DI BURSA EFEK INDONESIA - Veronica Napitupulu; Syahyunan Syahyunan (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT The purpose of this research is to investigate and analyze the effect of stock returns, stock trading volume and stock price volatility toward bid-ask spread on companies that doing stock split activity in the Indonesia Stock Exchange. Type of this research is asosiative research. The population that is used in this research is 20 companies that doing stock split activity in the Indonesia Stock Exchange with some criterias. Hypothesis testing uses multiple regression method, with significance level 5%. The results of this research indicates that stock returns, stock trading volume and stock price volatility simultaneously have significantly effect toward bid-ask spread in the stock on companies that doing stock split activity in the Indonesia Stock Exchange. Partially, stock trading volume has positive effect and not significant, and stock price volatility has negative effect and not significant, only the stock return has positive and significant effect toward bid-ask spread on companies that doing stock split activity in the Indonesia Stock Exchange. Keywords: stock return, bid-ask spread, stock split, stock trading volume, and stock price volatility.